“Breath figures” on leaf surfaces—formation and effects of microscopic leaf wetness - Burkhardt, Jürgen; Hunsche, Mauricio (Frontiers in Plant Science, 2013)
“Microscopic leaf wetness” means minute amounts of persistent liquid water on leaf surfaces which are invisible to the naked eye. The water is mainly maintained by transpired water vapor condensing onto the leaf surface and to attached leaf surface particles. With an estimated average thickness of less than 1 μm, microscopic leaf wetness is about two orders of magnitude thinner than morning dewfall. The most important physical processes which reduce the saturation vapor pressure and promote condensation are cuticular absorption and the deliquescence of hygroscopic leaf surface particles. Deliquescent salts form highly concentrated solutions. Depending on the type and concentration of the dissolved ions, the physicochemical properties of microscopic leaf wetness can be considerably different from those of pure water. Microscopic leaf wetness can form continuous thin layers on hydrophobic leaf surfaces and in specific cases can act similar to surfactants, enabling a strong potential influence on the foliar exchange of ions. Microscopic leaf wetness can also enhance the dissolution, the emission, and the reaction of specific atmospheric trace gases e.g., ammonia, SO2, or ozone, leading to a strong potential role for microscopic leaf wetness in plant/atmosphere interaction. Due to its difficult detection, there is little knowledge about the occurrence and the properties of microscopic leaf wetness. However, based on the existing evidence and on physicochemical reasoning it can be hypothesized that microscopic leaf wetness occurs on almost any plant worldwide and often permanently, and that it significantly influences the exchange processes of the leaf surface with its neighboring compartments, i.e., the plant interior and the atmosphere. The omission of microscopic water in general leaf wetness concepts has caused far-reaching, misleading conclusions in the past.